Integrasi Pendidikan Berbasis Lingkungan melalui Mata Pelajaran IPA sebagai Upaya Menanamkan Kesadaran Lingkungan Siswa Sekolah Dasar - Sukmarani, Dhuta; Istiningsih, Galih; Suryawan, Ari (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2017)
This study aims to examine the effect of integration of environment-based education in science subjects to environmental awareness of students in Muhammadiyah Integrated Islamic Elementary School Bandongan Magelang. This research uses pretest-posttest control group design. The population in this study is all students of Muhammadiyah Integrated Islamic Elementary School Bandongan Magelang with the number of 360 students. The samples were taken using simple random sampling technique, that is third and fifth grader students. Twenty students of Class IIIA and nineteen students of Class VB are taken as control group. Twenty students of Class IIIC and eighteen students of Class VA are taken as experimental group. Environmental awareness data was taken using a questionnaire. Hypothesis analysis in this study was conducted using non-parametric test, Mann-Whiteney by SPSS software. Based on the hypothesis test using Mann-Whiteney, it is known that the value of Asymp. Sig. (2-tailed) in grade III is 0.004 <0.05 while in grade V is 0.015 <0.05. Can be interpreted that there is a significant influence of integration of environment-based education through science subjects to environmental awareness of students in Muhammadiyah Integrated Islamic Elementary School Bandongan Magelang.